Application of electrostatic adsorption method to preparation of aldol condensation acid-base bifunctional catalyst

By using electrostatic adsorption method of hydroxyoxynegative ions and alkali metal ions on silica support, the problem of uncontrollable distribution of active species in traditional impregnation methods is solved, and the directional regulation of active sites and significant improvement of catalytic activity is achieved.

CN119608143APending Publication Date: 2025-03-14INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411811653.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The traditional impregnation method is uncontrollable when distributing metal elements on the surface of the carrier, resulting in migration, aggregation and loss of active species, reducing catalytic activity and anti-carbon deposit properties.

Method used

Through electrostatic adsorption of hydroxyoxyne negative ions and alkali metal ions on the silica support, the alkaline site is anchored on the surface of the carrier, enhancing the interaction between the active component and the carrier.

Benefits of technology

Directed regulation of active sites is achieved, the utilization rate of active sites is improved, and catalytic activity and carbon deposit resistance are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180690230000071
    Figure BDA0005180690230000071
  • Figure BDA0005180690230000072
    Figure BDA0005180690230000072
  • Figure BDA0005180690230000073
    Figure BDA0005180690230000073
Patent Text Reader

Abstract

The invention discloses an acid-base bifunctional catalyst for preparing (methyl) acrylate through aldol condensation by an electrostatic adsorption method and application of the acid-base bifunctional catalyst. By utilizing the electrostatic interaction of hydroxyl oxygen anions and active alkali metal ions on the silicon dioxide carrier, directional regulation and control of active sites are realized, the possibility of agglomeration, migration and loss of active components is reduced, and the utilization rate of the active sites is improved. Compared with a traditional impregnation method, the loading capacity of the alkali metal active component is reduced by about 1 / 2, and the activity is improved by about 50%. The method is simple in preparation, good in repeatability and suitable for large-scale industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method and application of an acid-base bifunctional catalyst for aldol condensation by an electrostatic adsorption method. Specifically, an acid-base bifunctional catalyst is used in the process of preparing methyl (meth)acrylate from methyl acetate (propionate) and formaldehyde. Compared with the traditional impregnation method, the catalyst prepared by the method has higher catalytic activity and atomic utilization in the aldol condensation reaction. The synthesis method provided by the present invention is simple and can be used for large-scale application. Background Art

[0002] In the technical field of preparing methyl (meth)acrylate by aldol condensation, the design and development of catalysts are still in the laboratory research stage. Among them, the catalyst that is most likely to be prepared and applied on a large scale is a supported catalyst that uses commercial silica as a carrier and introduces active components by wet deposition (such as impregnation). At present, the importance of alkali metals for this reaction is emphasized in the disclosed patents, so it is very important to develop new methods to introduce alkaline sites to improve catalytic performance. When the traditional impregnation method loads alkali metal elements onto the carrier, due to the inability to control the distribution of metal elements in the pores, during the heat treatment (such as drying, roasting, etc.), metal particles are easy to migrate, aggregate and grow and sinter, resulting in poor dispersion of metals on the carrier surface and low utilization of active species. In addition, the active species introduced by the simple impregnation method have weak interaction with the carrier. As the reaction proceeds, the active components on the surface of the carrier will easily migrate or even lose, resulting in decreased activity.

[0003] Based on the traditional impregnation method, in order to improve the catalytic activity and its anti-carbon deposition performance, researchers mostly use the method of adding additives, including CN112844356 A, CN111905780 A, CN109999922 A, CN109364908B, CN113751011A, CN116621701A, etc. By adding different functional additives during the active metal impregnation process, the dispersion state of the metal surface is improved, thereby regulating the acidity and alkalinity of the catalyst surface in the hope of improving the catalytic performance and anti-carbon deposition ability.

[0004] The additive introduction method used in the disclosed patent has a certain improvement effect on the distribution of active species on the carrier surface. However, the active species / additives loaded by the impregnation method are mainly physically adsorbed on the carrier surface, and it is impossible to achieve directional regulation of the active sites; in addition, the interaction between the active species and the carrier is weak. As the reaction proceeds for a long time, the physically adsorbed active components may migrate, aggregate or even lose, hindering its practical application.

[0005] In view of the current technological status, this patent aims to provide a method for preparing an acid-base bifunctional catalyst for aldol condensation using an electrostatic adsorption method. This method achieves directional regulation of active sites through the electrostatic adsorption of silica hydroxyl oxygen anions and alkali metals, strengthens the interaction between active components and carriers, and improves the utilization rate of active sites, thereby improving the activity and anti-carbon deposition performance of the catalyst. Summary of the invention

[0006] The present invention provides a method for preparing an acid-base bifunctional catalyst for aldol condensation by using an electrostatic adsorption method. The electrostatic adsorption characteristics of hydroxyl oxygen anions and alkali metal ions on the surface of a silica carrier in an alkaline environment are utilized to achieve directional regulation of active alkaline sites, avoid the migration and aggregation of active components, and improve the utilization rate of active sites.

[0007] An electrostatic adsorption method is applied to the preparation of an acid-base bifunctional catalyst for aldol condensation, characterized in that the alkaline sites are anchored on the surface of the carrier through the electrostatic interaction between the hydroxyl oxygen anions on the silica and the alkali metal ions, thereby strengthening the interaction between the active component and the carrier. The method comprises the following steps:

[0008] a) weighing a certain amount of acid metal and dissolving it in deionized water to prepare an acid metal salt solution of required concentration, placing the silica carrier in the above solution, standing and impregnating it at room temperature for 3-6 hours, and then placing it in an oven at 80-120° C. and drying it for 3-6 hours to obtain an acid deposition precursor;

[0009] b) placing the acid-deposited precursor obtained in step a) in a muffle furnace, setting a constant temperature increase program, and maintaining the temperature at 400-600° C. for 4-6 hours, and obtaining an acid-deposited modified carrier after natural cooling;

[0010] c) Weigh the required amount of alkali metal into a beaker, add an appropriate amount of water to dissolve it, and adjust the pH to ≥ 12.

[0011] Subsequently, the acid-deposited modified support obtained in step b) is mixed with the above-mentioned alkaline solution, and allowed to stand for adsorption at room temperature for 4-6 hours to obtain an electrostatically adsorbed precursor;

[0012] d) Pour the electrostatically adsorbed precursor into a Buchner funnel and repeatedly rinse the precursor with deionized water. When the pH of the filtrate is ≈ 7, stop washing. Collect the solid matter on the filter cloth and heat it at 80-120℃.

[0013] The mixture is dried at 400-600°C for 3-6 hours, and finally calcined at 400-600°C for 4-6 hours. After natural cooling, the desired acid-base bifunctional catalyst is obtained.

[0014] The specific surface area of ​​the silicon dioxide in step a) is 200-400m 2 / g, the maximum integrable pore size is 5-15nm;

[0015] The amount of the acid / alkali active metal added in steps a) and c) is 1-5% by weight of the acid metal and 1-5% by weight of the alkali metal based on the weight of the carrier.

[0016] The acid metal in step a) includes but is not limited to one or more of Al, Zr, Ti and the like, and its salt solution is an aqueous solution or alcohol solution of nitrate, sulfate, chloride of the corresponding element; the alkali metal in step c) is Cs, and its source is one or more of cesium carbonate, cesium acetate, and cesium hydroxide;

[0017] In the traditional supported catalyst, the distribution of metal on the support surface is uncontrollable during the impregnation process, and the active species are prone to migration and agglomeration to form aggregates, which reduces the catalytic activity. Even if the introduction of additives improves the above situation, it is still impossible to achieve directional regulation of active sites. For catalysts used for a long time, the active species physically adsorbed on the surface have the problem of migration or even loss when in contact with reactants / products;

[0018] The acid-base bifunctional catalyst provided by the present invention anchors the alkali metal on the surface of the carrier through electrostatic adsorption of hydroxyl oxygen anions and alkali metal ions on the silica carrier, strengthens the interaction between the alkali metal and the carrier, increases the utilization rate of the active base sites, and thus improves the catalytic performance of aldol condensation.

[0019] Compared with the existing catalyst preparation technology, the beneficial effects of the present invention are:

[0020] A method for preparing an acid-base bifunctional catalyst for aldol condensation by using an electrostatic adsorption method is proposed. The electrostatic effect between hydroxyl oxygen anions and active alkali metal ions on a silica carrier is used to achieve directional regulation of active sites, reduce the possibility of agglomeration, migration and loss between active components, increase the utilization rate of active sites, and improve the catalytic activity of aldol condensation to prepare methyl (meth)acrylate. The method for preparing the acid-base catalyst provided by the present invention is simple, low in cost, highly repeatable, and has high industrial application value. DETAILED DESCRIPTION

[0021] The present invention is described in more detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the invention, and any substitutions and changes without substantial changes made by relevant technicians in the field based on the general techniques and means in the field should be included in the scope of the present invention.

[0022] Example 1

[0023] Weigh 0.7 g of cesium hydroxide monohydrate and dissolve it in a certain amount of deionized water, weigh 10.0 g of silica carrier and add it to the above solution and let it stand for 6 hours, then wash the impregnated silica carrier with deionized water, collect the filter residue solid when the filtrate pH is ≈ 7, then dry it at 120°C for 6 hours, and finally calcine it at 500°C for 5 hours. After cooling, the catalyst is obtained, which is recorded as Cat-1.

[0024] Example 2

[0025] (1) 1.4 g of zirconium nitrate pentahydrate was weighed and dissolved in a certain amount of deionized water, 10.0 g of a silica carrier was weighed and added to the above solution and allowed to stand for 6 h, then dried at 120° C. for 6 h, and finally calcined at 500° C. for 5 h, and after cooling, an acid-deposited modified carrier was obtained;

[0026] (2) Weigh 0.7 g of cesium hydroxide monohydrate and dissolve it in a certain amount of deionized water. Add the modified support precipitated by acid in (1) to the above solution and let it stand for 6 hours. Then wash the impregnated precursor with deionized water. When the pH of the filtrate is ≈ 7, collect the solid residue, then dry it at 120°C for 6 hours, and finally calcine it at 500°C for 5 hours. The catalyst obtained after cooling is recorded as Cat-2.

[0027] Example 3

[0028] (1) Weighing 2.3 g of aluminum nitrate nonahydrate and dissolving it in a certain amount of deionized water, weighing 10.0 g of a silica carrier and adding it to the above solution, leaving it to stand for 6 h, then drying it at 120° C. for 6 h, and finally calcining it at 500° C. for 5 h, and cooling it to obtain an acid-deposited modified carrier;

[0029] (2) Weigh 0.7 g of cesium hydroxide monohydrate and dissolve it in a certain amount of deionized water. Add the modified support precipitated by the acid in (1) to the above solution and let it stand for 6 hours. Then wash the impregnated precursor with deionized water. When the pH of the filtrate is ≈ 7, collect the filter residue solid, then dry it at 120°C for 6 hours, and finally calcine it at 500°C for 5 hours. The catalyst obtained after cooling is recorded as Cat-3.

[0030] Example 4

[0031] (1) Weighing 0.7 g of zirconium nitrate pentahydrate and dissolving it in a certain amount of deionized water, weighing 10.0 g of a silica carrier and adding it to the above solution, leaving it to stand for 6 hours, then drying it at 120° C. for 6 hours, and finally calcining it at 500° C. for 5 hours, and cooling it to obtain an acid-deposited modified carrier;

[0032] (2) Weigh 0.7 g of cesium hydroxide monohydrate and dissolve it in a certain amount of deionized water. Add the modified support precipitated by the acid in (1) to the above solution and let it stand for 6 hours. Then wash the impregnated precursor with deionized water. When the pH of the filtrate is ≈ 7, collect the solid residue, dry it at 120°C for 6 hours, and finally calcine it at 500°C for 5 hours. The catalyst obtained after cooling is recorded as Cat-4.

[0033] Example 5

[0034] (1) 1.4 g of zirconium nitrate pentahydrate was weighed and dissolved in a certain amount of deionized water, 10.0 g of a silica carrier was weighed and added to the above solution and allowed to stand for 6 h, then dried at 120° C. for 6 h, and finally calcined at 500° C. for 5 h, and after cooling, an acid-deposited modified carrier was obtained;

[0035] (2) Weigh 0.4 g of cesium hydroxide monohydrate and dissolve it in a certain amount of deionized water. Add the modified support precipitated by the acid in (1) to the above solution and let it stand for 6 hours. Then wash the impregnated precursor with deionized water. When the pH of the filtrate is ≈ 7, collect the filter residue solid, then dry it at 120°C for 6 hours, and finally calcine it at 500°C for 5 hours. The catalyst obtained after cooling is recorded as Cat-5.

[0036] Comparative Example 1

[0037] 0.7 g of cesium nitrate was weighed and dissolved in a certain amount of deionized water, 10.0 g of silica carrier was weighed and added to the above solution and allowed to stand for 6 hours, then dried at 120° C. for 6 hours, and finally calcined at 500° C. for 5 hours. After cooling, a catalyst was obtained, which was recorded as Cat-I.

[0038] Comparative Example 2

[0039] (1) 1.4 g of zirconium nitrate pentahydrate was weighed and dissolved in a certain amount of deionized water, 10.0 g of a silica carrier was weighed and added to the above solution and allowed to stand for 6 h, then dried at 120° C. for 6 h, and finally calcined at 500° C. for 5 h, and after cooling, an acid-deposited modified carrier was obtained;

[0040] (2) Weigh 0.7 g of cesium nitrate and dissolve it in a certain amount of deionized water. Add the modified support deposited by acid in (1) to the above solution and let it stand for 6 hours. Then dry it at 120°C for 6 hours. Finally, calcine it at 500°C for 5 hours. After cooling, a catalyst is obtained, which is recorded as Cat-II.

[0041] Comparative Example 3

[0042] (1) Weighing 2.3 g of aluminum nitrate nonahydrate and dissolving it in a certain amount of deionized water, weighing 10.0 g of a silica carrier and adding it to the above solution, leaving it to stand for 6 h, then drying it at 120° C. for 6 h, and finally calcining it at 500° C. for 5 h, and cooling it to obtain an acid-deposited modified carrier;

[0043] (2) Weigh 0.7 g of cesium nitrate and dissolve it in a certain amount of deionized water. Add the modified support deposited by acid in (1) to the above solution and let it stand for 6 hours. Then dry it at 120°C for 6 hours. Finally, calcine it at 500°C for 5 hours. After cooling, a catalyst is obtained, which is recorded as Cat-III.

[0044] The contents of active metals in the catalysts obtained by the electrostatic adsorption method and the equal volume impregnation method were measured by inductively coupled plasma optical emission spectroscopy (ICP-OES), and some of the measurement results are shown in Table 1;

[0045] The activity of the catalyst was tested in a fixed bed microreactor. Specifically, the catalyst loading was 4 mL, the molar ratio of methyl acetate / formaldehyde was 1:1, the molar ratio of formaldehyde / methanol was 1:2, and the liquid hourly space velocity was 0.6 h -1 , the reaction temperature is 360℃, and the reaction results are shown in Table 2-5.

[0046] Table 1

[0047]

[0048] Table 2

[0049]

[0050] Table 3

[0051]

[0052] Table 4

[0053]

[0054] Table 5

[0055]

[0056] The comparative evaluation results of Cat-2 and Cat-II show that when the same content of acid / alkali metal is introduced, the catalyst activity and selectivity of the electrostatic adsorption method are significantly better than those of the equal volume impregnation method, and the catalytic performance is improved by about 50%. In addition, the above results can be proved by comparing Cat-1 with Cat-I, and Cat3 with Cat-III. The evaluation results of Cat-2, Cat-3 and Cat-1 prove that the introduction of acid metal is conducive to the improvement of catalytic performance. By comparing the results of Cat-2 with Cat-4 and Cat-5, it can be found that the appropriate acid-base site ratio has a significant effect on the catalytic performance of the aldol condensation to produce methyl (meth) acrylate.

[0057] The present invention provides an electrostatic adsorption method for preparing an acid-base bifunctional catalyst for aldol condensation, wherein the pH is adjusted to ≥ 12, and the electrostatic adsorption of hydroxyl oxygen anions and active alkali metal ions on a silica carrier is used to achieve directional regulation of the alkaline sites, reduce the possibility of agglomeration, migration and loss of active species, and improve the utilization rate of active sites. Compared with the traditional impregnation method, the loading amount of the alkali metal active component is reduced by about 1 / 2, and the activity is increased by about 50%. The method is simple to prepare and easy to repeat, and is suitable for industrial promotion.

Claims

1. An electrostatic adsorption method is applied to the preparation of an acid-base bifunctional catalyst for aldol condensation, the method comprising wet deposition of an acid metal, electrostatic adsorption of an alkali metal and ion removal treatment, characterized in that: 1) Acid metal wet deposition: a certain amount of acid metal is dissolved in deionized water to prepare a corresponding precursor solution, the silica carrier is immersed in the above solution for 3-6 hours, then dried at 80-120°C for 3-6 hours, and treated at 400-600°C for 4-6 hours, and then cooled to obtain an acid-deposited modified carrier; 2) Alkali metal electrostatic adsorption: Weigh the required mass of alkali metal salt and place it in a beaker, then add an appropriate amount of water to dissolve it, adjust the pH to ≥ 12, then immerse the acid-deposited modified support in the above alkali metal solution, and let it stand at room temperature for 4-6 hours to obtain a precursor treated by electrostatic adsorption; 3) Ion removal treatment: Place the precursor treated by electrostatic adsorption in a Buchner funnel, repeatedly rinse the precursor with deionized water, and stop washing when the pH of the filtrate is ≈ 7. Dry the collected filter residue solid at 80-120°C for 3-6h, and finally calcine at 400-600°C for 4-6h, and cool to room temperature to obtain the acid-base bifunctional catalyst required for the reaction.

2. The preparation method according to claim 1, characterized in that: The acid metal element in step 1) is one or more of Al, Zr, Ti, etc., and its salt solution is an aqueous solution or alcohol solution of nitrate, sulfate, chloride of the corresponding element; the alkali metal in step 2) is Cs, and its source is one or more of cesium carbonate, cesium acetate, and cesium hydroxide.

3. The preparation method according to claims 1 and 2, characterized in that: The amount of active components introduced in steps 1) and 2) is based on the mass of the carrier and is calculated on the mass of the acid / alkali metal elements. The amount of acid metal added is 1-5%, and the amount of alkali metal added is 1-5%.

4. A method for preparing methyl (meth)acrylate by aldol condensation, characterized in that: Methyl (meth)acrylate is prepared by gas phase condensation reaction of reaction raw materials containing methyl acetate (propionate), trioxymethylene and methanol prepared in a certain molar ratio on an acid-base bifunctional catalyst, wherein the acid-base bifunctional catalyst is the catalyst obtained according to claims 1-3.

5. The preparation method according to claims 1-3, characterized in that: According to steps 1) to 3) of claim 1, an acid-base bifunctional catalyst having a strong interaction between the active base site and the carrier can be obtained.

Citation Information

Patent Citations

  • Catalyst, preparation method thereof and application of catalyst in preparation of methyl methacrylate

    CN111905780A

  • Catalyst for synthesizing methyl methacrylate and application method thereof

    CN112844356A

  • High-stability catalyst for synthesizing methyl acrylate and preparation method of high-stability catalyst for synthesizing methyl acrylate

    CN104275172A

  • Vatalyst for aldol condensation reaction as well as preparation method and application of catalyst

    CN110694608A

  • Catalyst for synthesizing methyl acrylate or methyl methacrylate and application

    CN112221482A